Malfeasant bodies, Orientalism, and colonial image-making, 1850–1912. (2nd November 2017) - Allender, Tim
Abstract: Using a wide array of photographs and other examples of the visual, this article reveals the distinctive messaging of the image when situated within empire, with colonial India as a case study. The author analyses the making of the image in the hands of the colonial master but where it becomes uncontrollable, if not revelatory, in its messaging about the true nature of the colonial domain. Two main categories of image are examined. The first category is about the messaging around conventional transferrals of white culture and practices of rule. This is where messages are created about the colonial imposition that offer up favoured, yet flawed, projections of the European in empire. A second category, deeply about the interaction of the colonial body, is more penetrating. Here, the imagery around the malfeasant and disobedient "native" body reveals the complexity of entangled imperial race, culture, and gender imperatives. The image conveys insurgent messages about colonial rule and undoes the white cultural language of empire.